PENGARUH SISTEM PENGENDALIAN INTERNAL TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA - Jumarni; Zulfikar, Arya (Jurnal Nusa Akuntansi, 2025)
The purpose of this study is to determine whether the implementation of the internal control system and accountability has an effect on the management of village funds in Sumbawa District. The sample used was 35 respondents in 7 sub-districts in Sumbawa Regency, each sub-district was taken as many as 5 respondents. Based on research on the effect of the internal control system on the accountability of village fund management, it states that the internal control system has an effect on the accountability of village fund management. This is indicated by the significance value of 0.008 <0.05. Thus Ha is accepted and Ho is rejected. This means that there is a significant effect of the internal control system on the accountability of village fund management. In addition, based on the results of the determination coefficient test (R2) of 0.148, it can be concluded that the internal management system has a relationship of 14.8% to accountability. The remaining 85.2% is influenced by other variables not examined in this study